PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KOMITMEN MANAJEMEN PADA LABORATORIUM MAWAR - Fry Medistya Anke Priyono (Journal of Business & Banking, 2012)
It can be argued that current financial aspect is not a guarantee for a company which has good management for non-financial aspects. Therefore, such a condition requires a concept of balanced scorecard in a company, in this case, it is is a Laboratorium Mawar which is privately owned. Laboratorium Mawar tried to provide different styles of leadership to employees as a balancer of the financial aspect. Apparently, this affects job satisfaction nd employee commitment seriously so that there are four aspects of the balanced scorecard that can be balanced. Job satisfaction, for example, is a positive attitude toward work in individuals who are affected by two factors: maintenance factors and motivations factors. On the contrary, organizational commitment is the belief that strong values and organizational goals, willingness affect an extra effort in order to remain becoming a member or part of the organization. The four aspects that must be embodied in this concept include the financial, customer, internal business process and learning and growth so as to make the owner have a leadership style that makes employees comfortable in the work.